Submarine landform assemblages and sedimentary processes related to glacier surging in Kongsfjorden, Svalbard - Streuff, K.; Forwick, Matthias; Szczucinski, W.; Andreassen, Karin; O' Cofaigh, C. (arktos, 2015)
License: Creative Commons Attribution 4.0 International License (http://crea tivecommons.org/licenses/by/4.0/) Published version also available at http://dx.doi.org/10.1007/s41063-015-0003-y High-resolution swath-bathymetry data from inner Kongsfjorden, Svalbard, reveal characteristic landform assemblages formed during and after surges of tidewater glaciers, and provide new insights into the dynamics of surging glaciers. Glacier front oscillations and overriding related to surge activity lead to the formation of overridden moraines, glacial lineations of two types, terminal moraines, associated debris lobes and De Geer moraines. In contrast to submarine landform assemblages from other Svalbard fjords, the occurrence of two kinds of glacial lineations and the presence of De Geer moraines suggest variability in the landforms produced by surge-type tidewater glaciers. All the landforms in inner Kongsfjorden were deposited during the last c. 150 years. Lithological and acoustic data from the innermost fjord reveal that suspension settling from meltwater plumes as well as ice rafting are dominant sedimentary processes in the fjord, leading to the deposition of stratified glacimarine muds with variable numbers of clasts. Reworking of sediments by glacier surging results in the deposition of sediment lobes containing massive glacimarine muds. Two sediment cores reveal minimum sediment accumulation rates related to the Kongsvegen surge from 1948; these were 30 cm a-1 approximately 2.5 km beyond the glacier front shortly after surge termination, and rapidly dropped to an average rate of 1.8 cm a-1 in 1950, during glacier retreat.